Physical function mediates the effects of sensory impairment on quality of life in older adults: Cross‐sectional study using propensity‐score weighting. (25th August 2022) - Tseng, Ya‐Chuan; Gau, Bih‐Shya; Hsieh, Yeu‐Sheng; Liu, Tien‐Chen; Huang, Guey‐Shiun; Lou, Meei‐Fang
Abstract: Aims: To investigate the effect of sensory impairment on quality of life in older adults and to assess the role of physical function as a mediator of the effect of the sensory impairment on quality of life. Design: A cross‐sectional study. Methods: Older adults aged ≥65 years ( N = 600) were recruited from January 2019 to May 2020. Hearing and visual function were measured with pure‐tone audiometry and Snellen visual acuity tests, respectively. Quality of life (World Health Organization Quality of Life Scale Brief Version), physical function (Multidimensional Functional Assessment Questionnaire) and sociodemographic characteristics were reported by participants using interviewer‐administered questionnaires. Propensity score weighting analysis was conducted based on generalized propensity scores via multinominal logistic regression for age, gender, education, income, and comorbidities. The difference in the quality of life was tested by applying a one‐way analysis of variance. Multiple mediation analysis was conducted to explore the direct, indirect, and total effects of sensory impairment on quality of life through physical function. Results: After propensity score weighting adjustment, when compared with participants with no sensory impairment, participants with dual sensory impairment had the worst quality of life, followed by visual impairment and then hearing impairment. Physical function statistically significantly mediated the effect of hearing impairment, visual impairment and dual sensory impairment on quality of life in older adults. Conclusion: Our findings demonstrated that the negative effect of the sensory impairment on quality of life in older adults was mediated through physical function. Impact: The convergence of an increasing ageing population and the prevalence of sensory impairment presents a significant global health burden. This study demonstrated that physical function was a mediator of quality of life in older adults. Designing appropriate physical activity interventions for older adults with sensory impairment could serve to enhance physio‐psychological health and improve quality of life.